2021
DOI: 10.3390/tomography7030023
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Errors in Pharmacokinetic Parameters from Analyzing Quantitative Abbreviated DCE-MRI Data in Breast Cancer

Abstract: This study characterizes the error that results when performing quantitative analysis of abbreviated dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) data of the breast with the Standard Kety–Tofts (SKT) model and its Patlak variant. More specifically, we used simulations and patient data to determine the accuracy with which abbreviated time course data could reproduce the pharmacokinetic parameters, Ktrans (volume transfer constant) and ve (extravascular/extracellular volume fraction), when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Temporal under-sampling known to poorly affect the accuracy of K trans estimation, 8 and fit accuracy is decreased with few dynamic acquisitions. 36 As K trans measurement is highly sensitive to sampling rate and the ability to capture the peak of the VIF, 36 we recommend that studies aimed at measuring K trans accurately and repeatably, do so in accordance with the QIBA recommendations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Temporal under-sampling known to poorly affect the accuracy of K trans estimation, 8 and fit accuracy is decreased with few dynamic acquisitions. 36 As K trans measurement is highly sensitive to sampling rate and the ability to capture the peak of the VIF, 36 we recommend that studies aimed at measuring K trans accurately and repeatably, do so in accordance with the QIBA recommendations.…”
Section: Discussionmentioning
confidence: 98%
“… 9 Temporal under-sampling and limited dynamic acquisitions are known to poorly affect the accuracy of K trans estimation. 8 , 36 DCE imaging quality is critical for advancing tumor assessment methods in clinical trials designed to use DCE parameters (such as K trans ) as end points. The recently published ACRIN 6686 trial showed rCBV, but not K trans , to be a sensitive biomarker of early biological changes following bevacizumab treatment in newly diagnosed GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in quantitative perfusion assessments-such as measures of contrast agent kinetics-can characterize tumor physiology. [8][9][10] These have been demonstrated in the community setting [11][12][13] and have been shown to provide additional specificity for both diagnostic [14][15][16][17][18] and prognostic application. 19,20 The challenge in adding quantitative DCE MRI to a SOC exam is that it requires imaging with temporal resolution that is about 10 times faster than SOC scans, during the same 5-7-min postcontrast injection window (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in quantitative perfusion assessments—such as measures of contrast agent kinetics—can characterize tumor physiology 8–10 . These have been demonstrated in the community setting 11–13 and have been shown to provide additional specificity for both diagnostic 14–18 and prognostic application 19,20 …”
Section: Introductionmentioning
confidence: 99%